TRANSPARENCY AND ACCOUNTABILITY OF VILLAGE GOVERNMENTS IN THE MANAGEMENT OF VILLAGE ALLOCATIONS OF ISLAMIC PERSPECTIVE - Ratna Sari Dewi; Asmuni Asmuni; Muhammad Yafiz (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine the transparency and accountability of the village government in managing the Village Fund Allocation (ADD). This type of research uses qualitative methods. The case study referred to is that the researcher aims to provide a clearer picture of more specific social situations by focusing on the management of Village Fund Allocation (add). The results show that the implementation of the principles of transparency and accountability of the village government in managing the Village Fund Allocation (ADD) is in accordance with Permendagri number 113 of 2014. The village government has proven its commitment or responsibility by complying with and following the stages and provisions that apply in accordance with the regulations has been stipulated in Permendagri number 113 of 2014. Keywords: Transparency, Accountability, Village Fund Allocation